BELEZA SUSTENTÁVEL E COMUNIDADES DE MARCA: O PAPEL DO CONSUMO CONSCIENTE NA CONSTRUÇÃO DE RELAÇÕES DE VALOR (DAPesquisa, 2025)
Sustainable brands in the beauty sector build symbolic relationships and engaged communities through conscious consumption and marketing strategies aligned with sustainability principles. This article aims to identify how sustainable practices and emotional marketing strategies contribute to the development of brand communities in the beauty segment. The research adopts a qualitative approach and a descriptive character, conducted through a literature review and a case study of the brand Simple Organic. The findings indicate that authentic sustainable actions strengthen consumer bonds and foster positive transformations in the beauty market. Keywords: Conscious consumption; Sustainability; Brand communities; Sustainable marketing; SAVE approach.